Vibrio cholerae: epidemiology of Cholera, virulence, ecology, biofilms and vibrio phages - Islam, Anik Dibya; Sajida, Syeda Saima (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.